John Dewey, Albert Barnes, and the Continuity of Art and Life - Granger, David A. (Peter Lang Inc., 2023)
This carefully researched book offers a dynamic and expansive Deweyan vision for the arts and education. This (re)vision acknowledges the influence on Dewey’s aesthetics of art collector and educator Albert Barnes, while also exploring the various ways Dewey’s writings on the arts, in moving beyond Barnes’
10.3726/b20366
Keywords: Dewey; John; Barnes; Albert C.; Künste; Kunsterziehung; Ästhetik; (Albert) Barnes; (Allan) Kaprow; (Henri) Matisse; (Jackson) Pollock; (John) Cage; (John) Dewey; (Josef) Albers; (Marcel) Duchamp; (Merce) Cunningham; (Robert) Rauschenberg; (Thomas Hart) Benton; Albert; art; Arts; Barnes; Barnes Foundation; Black Mountain College; Continuity; Dani; David; David A. Granger; Dewey; Education; education; Granger; Green; John; John Dewey; Albert Barnes; and the Continuity of Art and Life; Life; Revisioning; Revisioning the Arts and Education